Pengaruh Penerapan Kebijakan Low Emission Zone terhadap Perubahan Perilaku Perjalanan Komuter di Kawasan Kotatua Jakarta - Syafitri, Anindya Shilviana; Dirgahayani, Puspita (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Along with the increasing population growth of DKI Jakarta, the need for transportation services is also increasing. This has resulted in a growth in the number of motorized vehicles, the high number of private vehicles in DKI Jakarta causes many transportation problems as well as will increase the number of air pollutants that can pollute the air and have a negative impact on the environment and air quality, one of the government policies that began to be implemented to reduce the use of private vehicles while reducing air pollution is the implementation of the Low Emission Zone (LEZ) policy in Kotatua Jakarta, with this policy with this policy, it is expected that people will reduce the use of private vehicles and shifting to public transportation. This study aims to determine the effect of the implementation of the LEZ policy on changes in travel behavior and identify factors that influence mode selection preferences using the binary logit regression method, after the implementation of the LEZ policy there are a change in commuter travel behavior in including the percentage of respondents from West Jakarta increased by 7%, the dominant shift in modes used by respondents from private vehicles to Public transportation as 21.42%, it was also seen that the use of private vehicles such as motorcycles and private cars decreased from 62.14% to 42.85%, there was a decrease in travel costs and an increase in travel time while factors that influenced the choice of mode preferences included education level, income, travel patterns and travel costs. Keyword : binary logit, Low Emission Zone, mode preference